(untitled) (Boletin Médico de Postgrado, 2024)
Laparoscopic cholecystectomy is the treatment of choice for biliary lithiasis and is recognized as an effective and safe procedure for elective and emergency resolution. In certain cases it is necessary to convert laparoscopic cholecystectomy to an open approach. The objective of the present study was to evaluate the experience in laparoscopic cholecystectomy and its conversion at the Ana Francisca Perez de Leon II Hospital. The research was observational, descriptive, retrospective and cross-sectional. A total of 391 patients were included in the study. The main form of admission was elective (95.1%) and the predominant sex was female (89.7%). Conversion was required in 3.3% of cases. Cholecystectomy conversion was more frequent in emergency patients, men (p=0.006) and age over 50 years; conversion conditioned longer hospital stay (p=0.009) and operative time. The main cause of cholecystectomy conversion was laparoscopic equipment failure. It is possible to affirm that the rate of conversion from laparoscopic to open cholecystectomy documented in the present study is on a par with the results achieved by different researchers on an international scale.